Budaya Religius dalam Menguatkan Pendidikan Toleransi dan Harmoni Siswa Muslim dilingkungan Sekolah - Nurhasanah, Muwahidah; Sumarno, Sumarno; Bermi, Wibawati (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study investigates the role of religious culture in fostering tolerance and harmony within Muhammadiyah schools. By examining how religious values are integrated into daily school life, the research aims to understand how these values can promote mutual respect and cooperation among students from diverse backgrounds. The study employs a qualitative approach, using phenomenological analysis to explore the experiences of students and educators in these schools. Findings suggest that religious culture, when implemented inclusively, can serve as a powerful tool for cultivating tolerance and creating a more harmonious learning environment. The study highlights the significance of religious activities and the emphasis on human values in Islamic teachings as key factors in promoting positive social interactions and reducing conflicts based on differences. Ultimately, this research contributes to the understanding of how religious culture can be leveraged to strengthen educational outcomes and create more inclusive and peaceful school communities.